EP170/#317 Facilitated cascade testing for families with identified mutations associated with hereditary gynecologic cancers. (4th December 2022) - Lee, Sarah; Karpel, Hannah; Brown, Ashley; Smith, Maria; Smith, Julia; Pothuri, Bhavana
Abstract : Objectives: We evaluated the feasibility of a facilitated referral pathway for cascade genetic testing (GT) for patients with mutations associated with gynecologic cancers. Methods: This is a prospective cohort study of patients with BRCA1, BRCA2, BRIP1, MSH2, MLH1, MSH6, PMS2, EPCAM, RAD51C, and RAD51D mutations from March 2019-March 2022. Eligible patients were offered a facilitated referral pathway for GT for first and second-degree relatives ( figure 1 ). Decision Regret Scale and Impact of Events Scale assessed psychological impact at 3-months. The primary outcome was the proportion of patients with a relative who successfully completed GT. Results: Of 583 eligible patients, 73 (13%) enrolled in our study. Reasons for declining participation were: no eligible relatives or previously tested (235, 40%), lost to follow-up (105, 18%), does not want to discuss GT with family (55, 9%), relatives not interested (50, 9%), language (38, 7%), and other (27, 5%). Of 73 enrolled patients, 45 (62%) contacted at least one relative to discuss GT within two months of enrollment. Twelve patients had at least one relative who participated in our facilitated referral pathway, but only 2 (3%) relatives completed GT through our pathway. Two additional relatives underwent GT separately. Of 20 patients who completed 3-month psychological impact questionnaires, 13 (65%) had no regret, and 19 (95%) had none to subclinical range stress. Conclusions: Although over 50% of patients contacted family members regarding GT, only 3% had a relative undergo GT via our facilitated referral pathway. Comprehensive novel efforts to simplify access to GT for relatives are desperately needed.